1983
DOI: 10.1073/pnas.80.19.5822
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of monoclonal antibodies directed against the DNA repair enzyme uracil DNA glycosylase from human placenta.

Abstract: A series of monoclonal antibodies has been prepared against the base excision repair enzyme uracit DNA glycosylase isolated from human placenta. Spleen cells from BALB/ c mice immunized with purified human placentaluracil DNA glycosylase were fused with either P3X63 Ag8.653 or SP2/0 myeloma cells. Hybridomas producing antibodies directed against the placental glycosylase were identified in an enzyme-linked immunosorbent assay. Each positive hybridoma was cloned twice by limit dilution and tested for anti-glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Several eukaryotic DNA polymer- 16.11.08 (95 Ag) for 120 min at 40C. The enzyme/antibody mixture was then sedimented through a 5-ml 10-35% glycerol gradient as described (5). Highly purified Bacillus subtilis uracil DNA glycosylase was a generous gift of Nahum Duker.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several eukaryotic DNA polymer- 16.11.08 (95 Ag) for 120 min at 40C. The enzyme/antibody mixture was then sedimented through a 5-ml 10-35% glycerol gradient as described (5). Highly purified Bacillus subtilis uracil DNA glycosylase was a generous gift of Nahum Duker.…”
Section: Discussionmentioning
confidence: 99%
“…Human placental uracil DNA glycosylase was partially purified through DEAE-cellulose, phosphocellulose, and hydroxylapatite column chromatography as described (5 centrifugation at 2300 x g for 10 min at 4°C. The precipitate was redissolved and reprecipitated twice using 1 ml of 0.2 mM NaOH and 1 ml of 10% trichloroacetic acid, sequentially, followed by centrifugation as described above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of monoclonal antibodies was prepared against the partially purified human placental uracil DNA glycosylase (17). Subsequent analysis showed that each antibody recognized determinants on the homogeneous placental enzyme (18).…”
mentioning
confidence: 99%